Field Education Challenges: Science teaching and the reality of the Santo Antonio community (Research, Society and Development, 2020)
The main objective of this research was to analyze the difficulties faced by students in contextualizing the contents of the 9th of Elementary School Natural Sciences with the local reality and specific of the Santo Antônio community, at the Santo Antônio Annex multiseriate school. Through a field research with a qualitative approach, was interviewed fathers and students and also documentary research was done. The results indicate that the rural schools are not prepared to contribute to the development of individuals in order to give a perspective of the contents to their way of life, and may directly influence the learning process of and the campo students, and may discourage them. It was identified that the lack of training of professional affect the preparation of classes appropriate to the wishes of students and the community. In addition, the heterogeneity of class, content and age range was one of the main reasons for the difficulty in performing school planning, resulting in classes in the seriate model. It also highlights the need for the school and community to be partners not only in the formation of scientific knowledge, but also in their valorization through Curricular Planning that contextualizes with the reality of the community, based on its culture and experiences. Thus, the education the campo needs to be committed to a curriculum planning that brings meanings to students' lives as subjects of the field, so that their culture is valued and used as a basis in the construction of teaching and learning, seeking strategies that contemplate the identity of the student country man.